Forests and Floods - Ghosh, R. C.; Subba, B. K. (Indian Forester, 1979)
The role of forest in moderatiag the flood is briefly examined. The results or the important investigations carried out in India so far, have been sumrnarised. It is emphasised that watershed management shuld be tackled taking the watershed as a whole, and the flood control measures should be judicious combination of both vegetetion and engineering measures, The importance of vegetation cover in soil and water conservation, flood moderation and improving the water quality should be readised by all concerned.